EFFECT OF DIET ON CONTINUOUS GLUCOSE PROFILE OF HEALTHY INDIVIDUALS WITHOUT DIABETES - Khoo, Jonathon; Low, Serena; Sum, Chee Fang; Subramaniam, Tavintharan; Lim, Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES It is essential to understand continuous glucose monitoring (CGM) data in healthy subjects without diabetes which could serve as useful reference for interpretations of glucose measurements in diabetic patients. However, little is known about dietary impact on CGM data in studies of CGM in healthy individuals. We aim to characterise the effect of diet on interstitial glucose levels in healthy individuals without diabetes. METHODOLOGY We conducted a cross-sectional on 95 healthy volunteers without diabetes (mean age 34.9 ± 10.0 years) who underwent flash glucose monitoring using Freestyle Libre. Nutrient data collected from a food diary were analysed using FoodWorks Professional nutrient analysis software. Linear regression was performed to examine association between nutrient contents with peak glucose and 4-hr post-absorptive glucose levels, adjusting for demographics, body mass index, fasting plasma glucose and exercise. RESULTS The mean peak glucose and 4-hr post-absorptive glucose levels were 6.9 ± 1.7 and 4.6 ± 1.0 mmol/l. Higher levels of calorie, fat, carbohydrates and starch intake were associated with peak glucose levels in crude and fully adjusted analyses with adjusted coefficients 0.39 (95% CI 0.26-0.51; p<0.001), 0.21 (95% CI 0.08-0.34; p=0.001), 0.39 (95% CI 0.26-0.51; p<0.001) and 0.41 (95% CI 0.12-0.38; p<0.001) respectively. Higher levels of calorie, carbohydrates and sugar were associated with 4-hr post-absorptive glucose levels in crude and fully adjusted analyses with adjusted coefficients 0.13 (95% CI 0.06-0.21; p=0.001), 0.12 (95% CI 0.04-0.20; p=0.002) and 0.10 (95% CI 0.02-0.17; p=0.012) respectively. CONCLUSION Meals with higher calorie, fat, carbohydrates and starch intake induced higher peak glucose levels. Meals with higher levels of calorie, carbohydrates and sugar intake induced higher post-absorptive glucose levels.